Genome-Wide Studies on the Molecular Functions of Pax7 in Adult Muscle Satellite Cells - Punch, Vincent (Université d'Ottawa / University of Ottawa, 2011)
Pax3 and Pax7 belong to a family of conserved transcription factors that play important and diverse roles in development. In the embryo, they carry out similar roles in neural and somite development, but Pax7 fails to compensate for critical functions of Pax3 in the development of limb musculature. Conversely, in the adult, Pax7 is necessary for the maintenance and survival of muscle satellite cells, whereas Pax3 cannot effectively fulfill these roles in the absence of Pax7. To identify the unique roles of Pax7 in adult muscle cells, we have analyzed global binding of Pax3 and Pax7 by ChIP-Seq. Here, we show that despite highly homologous DNA-binding domains, the majority of binding sites are uniquely recognized by Pax7 and are enriched for homeobox motifs. Genes proximal to conserved, unique Pax7 binding sites cluster into specific functional groups which may reflect the unique biological roles of Pax7. Combining Pax7 binding sites with gene expression data, we describe the regulatory networks directed by Pax7 and show that Pax7 binding is associated with positive gene regulation. Moreover, we show Myf5 is a direct target of Pax7 and identify a novel binding site in the satellite cell control region upstream of Myf5.
Keywords: Pax7; Skeletal muscle; Transcriptional networks; Satellite cells; Stem cells; Regeneration